Pengaruh Current Ratio (CR) dan Debt To Equity Ratio (DER) Terhadap Return On Equity (ROE) Pada Perusahaan PT. Hanjaya Mandala Sampoerna Tbk - rijal, samsu; Nurul Huda; Amirul Mukminin (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The phenomenon in this research lies in the value of Current Debt and Total Debt at PT. Hanjaya Mandala Sampoerna Tbk, which continues to experience an increase from 2016 to 2022, this phenomenon of increasing debt has the potential to reduce the company's Profitability (Return On Equity). This is the basis and aim of this research, to see whether there is an influence of the Current Ratio and Debt to Equity Ratio on Return On Equity in PT companies. Hanjaya Mandala Sampoerna Tbk, either partially or simultaneously. This research uses purposive sampling in sample selection, and this research also uses multiple linear regression analysis. The results of this research show that partially the Current Ratio has a significant effect on Return On Equity, and the Debt to Equity Ratio has a significant effect on Return On Equity. Meanwhile, simultaneously the Current Ratio and Debt to Equity Ratio have a significant effect on Return On Equity